Effect of Noise Pollution on the Health of Techniciansat Dental Laboratories in Duhok City Kurdistan Region of Iraq (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Noise pollution is one of the disturbing noise that may harm the activity of human life. Dental technicians are exposed to diverse noise levels while working in dental laboratories due to using different dental instruments. The purpose of this work is to evaluate the sound pressure levels and its effects on the systolic and diastolic blood pressure , heart pulse rate , blood oxygen concentration , and hearing threshold level for 20 technicians working  in thegovernmental dental hospital and the most five popular  laboratories  in Duhok city, in Kurdistan region of Iraq.The mean sound pressure level values in all studied laboratories were ranged between 56.6 and 68.7 dB(A), whereas the maximum sound level wasranged between 76.7 and 99 dB(A).The results of this study refers to existence of a significant relation correlated positively (P-value < 0.050)  for each of HTL at some frequencies for both right and left ear, DBP and HPR while there was no a significant relation (P-value) for SBP and SpO2 %.